Healing while parasitized: impact of a naturally‐occurring nematode during energy‐intensive wound‐healing in a beetle. (16th December 2019) - Davis, Andrew K.; Calderon, Lexi; Lefeuvre, Jake; Sims, Stuart; Pearce, Jana; Prouty, Cody
Abstract: The rigours of the daily lives of insects sometimes lead to minor injuries and wounds, which must be healed to avoid entry of pathogens and to resume normal function. Such healing requires energy, which must be diverted from other bodily reserves. What happens if energy reserves are already low, as would occur in individuals coping with internal parasites? This question is addressed in the presemt study, using horned passalus beetles ( Odontotaenius disjunctus ) and their naturally‐occurring nematode Chondronema passali . Oxygen consumption rates are tested at rest, as well as after an experimental wound is applied, to evaluate energy requirements of wound‐healing in parasitized and nonparasitized hosts. Furthermore, wound‐healing rates are visually tracked with a numerical scoring system to directly measure the cost of parasitism on healing. At rest, parasitized beetles show no elevation in respiration (oxygen consumption). After wounding, the oxygen consumption of parasitized beetles is 10% higher than that in nonparasitized beetles. Beetles with moderate‐ to heavy worm burdens have slower healing than those with few or no nematodes. These results show that this parasite carries little cost to the host during day‐to‐day activities, whereas, during times of immediate energy demand, there is a cost; hosts require more energy to repair wounds, and the wounds take longer to close. This conclusion leads to the question of whether this parasite is truly benign, and how many other apparently benign parasites, in insects or other animals, have similar 'hidden' effects. Abstract : We experimentally examine whether an insect (bess beetle) with an abundant internal (nematode) parasite can effectively heal a wound At rest, nematode parasites do not elevate host oxygen consumption rates, although rates are 10% higher than normal when hosts are healing a wound Wound closure rates are slower in heavily‐parasitized hosts